Attitudes Towards Sexuality in Males and Females with Intellectual Disabilities: Indonesia Setting - Winarni, Tri Indah; Hardian, Hardian; Suharta, Suharta; Ediati, Annastasia (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
Introduction: sexual and reproductive rights in individuals with intellectual disabilities (ID), particularly in developing countries, are often neglected. Although affected individuals never complained, the problems were found augmented from the affected families. Over the last two decades, parents and professionals acknowledged sexual and reproductive right and try to accommodate these needs. Indonesia, a developing country with a strong religious and culture beliefs may has different perspectives on attitudes towards sexuality in individuals with ID which respect the sexual and reproductive right augmented from the affected family. The aimed of this study was to explore the attitudes towards sexuality on individuals with ID. The findings are expected to contribute to the movement in recognizing sexual and reproductive health and rights (SRHR) in individuals with ID. Methods: thirty participants were included in this study consisted of supporting staffs of rehabilitation center for disabled individual, parents, religious leaders and community. Participants fulfilled the two sets of Attitude to Sexuality Questionnaires towards individuals with ID (ASQ-ID). Results: the attitudes towards sexuality in males were found similar with females with ID, age did not play a role in the attitude towards sexuality in ID. Indonesian attitudes towards sexuality in individuals with ID was found the most conservative compared to other countries with the mean of sexual right was 3.7±0.22, parenting was 3.5±0.30, non-reproductive sexual behavior was 3.4±0.49, and self-control was 3.4±0.73. Conclusion: the attitudes towards sexuality in individual with ID is somewhat negative, strong culture and religious beliefs /and values may have strong influence.